Manipulating reference states: The effect of attitudes on utility - Astrid Matthey (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In economic theory, utility depends on past, present and future outcomes. The experiment described in this paper suggests that utility also depends on people's attitudes, and that it can easily be manipulated through these attitudes. The results imply, first, that purely outcome-based models of individual utility may be incomplete. Second, that reference-states are not determined completely endogenously but can be influenced from outside. And third, that experiments in economics may be sensitive to subtle details of the experimental design.
Keywords: D01; D10; C91; 330; Utility; reference state; attitudes; priming; experiment; Nutzen; Meinung; Präferenztheorie; Manipulation; Test